2003
DOI: 10.1038/sj.bmt.1703879
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage caused by cytomegalovirus and human herpesvirus-6

Abstract: Summary:Infection with cytomegalovirus (CMV) or human herpesvirus-6 (HHV-6) may have a role in vascular endothelial damage after bone marrow transplantation (BMT). In total, 41 patients who underwent BMT were classified into four groups (12, 10, 7, and 12 patients who were infected with both CMV and HHV-6, CMV alone, HHV-6, and neither virus, respectively). Levels of thrombomodulin, plasminogen activator inhibitor-1, and cyclic GMP were 7.571.7 FU/ml, 76.4724.1 ng/ml, and 9.5171.1 pmol/ ml, respectively, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 24 publications
1
52
1
Order By: Relevance
“…19 Gastrointestinal damage due to preparative regimens might contribute to the development of intestinal TMA in our study. CMV infection, which is another putative etiology of TMA, 17 was Table 3 Summary of macroscopic and pathological findings documented in four patients, and all were located in the gut. CMV colitis might be associated with intestinal TMA following RI-CBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Gastrointestinal damage due to preparative regimens might contribute to the development of intestinal TMA in our study. CMV infection, which is another putative etiology of TMA, 17 was Table 3 Summary of macroscopic and pathological findings documented in four patients, and all were located in the gut. CMV colitis might be associated with intestinal TMA following RI-CBT.…”
Section: Discussionmentioning
confidence: 99%
“…2,12 There is little information on the pathogenesis of intestinal TMA following RI-CBT. TMA after myeloablative HSCT has a multifactorial etiology that includes immunosuppressive agents, 14,15 total body irradiation (TBI), 16 CMV infection, 17 and acute GVHD. 18 These factors injure the vascular endothelium of many organs.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] This is possibly caused by the low number of patients and variation in the conditioning regimens. In vitro data showed that HHV6 can infect hematological progenitor cells and reduce colony formation, which may explain the delayed engraftment after HSCT.…”
Section: Incidence Of Hhv6 Reactivation and Clinical Manifestations Amentioning
confidence: 99%
“…[68][69][70][71][72] CMV or human herpes virus-6 in post-alloBMT patients may also cause vascular endothelial injury, which could lead to development of thrombotic microangiopathy. 73 Cytokine-induced thrombocytopenia It is possible that similar mechanisms are responsible for the thrombocytopenia in infection and cGVHD. Serum cytokine levels including granulocyte colony-stimulating factor (G-CSF), macrophage CSF (M-CSF), interleukin1a, interleukin-1b, and interleukin-6 may be significantly increased in both conditions, and may lead to the activation of monocytes and macrophages, leading to the increased platelet consumption.…”
Section: Immune-mediated Thrombocytopeniamentioning
confidence: 99%